Dose intense, dose dense and tailored dose adjuvant chemotherapy for early breast cancer: an evolution of concepts. (2nd September 2017) - Matikas, Alexios; Foukakis, Theodoros; Bergh, Jonas
Abstract: Background: The introduction of adjuvant chemotherapy following surgery for early breast cancer (BC) and its integration into routine clinical practice has consistently improved clinical outcomes. Since the addition of other agents to the contemporary standard of care containing an anthracycline, cyclophosphamide and a taxane has not lead to further prolongation of survival, subsequent efforts concentrated on escalating the administered doses and reducing the time interval between chemotherapy cycles. These strategies have been extensively evaluated in randomized trials and dose dense chemotherapy is now recommended by clinical practice guidelines. Method: Eligible trials were identified by searching the EMBASE, Pubmed, Scopus and Cochrane Library databases, as well as conference papers. The findings, shortcomings and impact of these studies are presented and critically discussed. Results: Although a large number of randomized trials has established the value of adjuvant chemotherapy, important questions remain unanswered. Ongoing research focuses on omitting treatment in good risk patients, identifying patients most likely to benefit from a dose dense approach and on administering personalized doses such as in tailored dose chemotherapy. Conclusions: Adjuvant chemotherapy for early BC is an evolving art. Further optimizations could potentially improve outcomes for a patient subset and spare others from unnecessary treatment-related toxicity.